Individualism/collectivism and perceived consumer effectiveness: The moderating role of global–local identities in a post‐transitional European economy. Issue 2 (27th September 2021) - Czarnecka, Barbara; Schivinski, Bruno
Abstract: What explains why some consumers believe their individual consumption choices impact the natural environment, social issues, and employee well‐being and others do not? This study examines the moderating role of global and local social identities on the relations between cultural values of vertical and horizontal individualism and collectivism, and perceived consumer effectiveness. Data were collected from 432 respondents in Poland. Individuals who report high values of vertical individualism and high vertical collectivism believe their individual purchase decisions impact the natural environment, social and community issues and employee welfare. It is the acceptance of responsibility for oneself (vertical individualism) and others (vertical collectivism) that explains why some people believe their consumption choices affect wider societal and environmental issues. Global identity strengthens this for vertical individualists, and local identity strengthens this for vertical collectivists. We provide evidence that the conceptual distinction between horizontal and vertical orientations of individualism and collectivism matters when explaining perceived consumer effectiveness. The study confirms that global and local social identities are meaningful variables in the context of perceived consumer effectiveness. The concept of value congruence explains the hypothesised relations only partially. The study contributes to the literature on consumer behaviour in the context of the post‐transitional economy of Poland.